Insecticide Efficacy Against Trimen’s False Tiger Moth, Agoma trimenii (Lepidoptera: Agaristidae) - Morris, C.; Malan, A.P.; De Waal, J.Y.; Johnson, S.A. (South African Journal of Enology and Viticulture, 2022)
Trimen’s false tiger moth, Agoma trimenii (Lepidoptera: Agaristidae), has developed pest status in vineyards in the Northern Cape and Groblersdal areas of South Africa, and an integrated pest management system is required. The objective of this study was to test the susceptibility of A. trimenii larvae to three commercial products (Delegate®WG, Steward®150 EC and three doses of DiPel® DF). Bioassay tests using all three products, and semi-field trials to test the potential of DiPel® DF against A. trimenii larvae, applied at different water volumes (50 g/1 000 L/ha and 50 g/1 430 L/ha) were performed. The residual activity of DiPel® DF, when applied at different water volumes, was investigated daily. Delegate® WG, Steward®150 EC and the recommended dose of DiPel® DF showed 100% larval mortality within seven days. Delegate® WG and the recommended dose of DiPel® DF proved to be the fastest acting products. The product label recommended dose of DiPel® DF (0.25 g/500 mL distilled water) proved the most effective dose (in comparison to halved and doubled dosages) and showed 100% mortality five days after application. Increasing the water volume per ha of a spray application of DiPel® DF for the same application area, showed no significant increase in larval mortality. A reduction in insecticidal activity for DiPel® DF applied at both water volumes was seen between leaves picked four days after spraying and leaves picked five days after spraying, and no mortality was observed after day 6. To help improve efficacy, attention should be given to increasing spray coverage and residual activity of DiPel® DF, as well as using all tested products within an integrated pest management system.